Hemispherical Cell-Inspired Soft Actuator - Song, Kahye; Cha, Youngsu (Frontiers in Bioengineering and Biotechnology, 2020)
As soft robots have been popular, interest in soft actuators is also increasing. In particular, new types of actuators have been proposed through bio mimetic. An actuator that we proposed in this study was inspired by a motor cell which enables plants to move. This actuator is an electrostatic actuator utilizing electrostatic attraction and elastic force, and can be used repeatedly. In addition, this actuator, which can produce large and diverse movements by collecting individual movements like a cell, has a wide application field. As one of them, this actuator is stacked to construct a layer structure and propose an application example. In addition, a piezo sensor was built inside the actuator and real - time motion monitoring was attempted. As a result, the point laser sensor value and the piezo sensor value coincided with each other, which means that it is possible to detect motion in real time with the built-in sensor.